2018
DOI: 10.1029/2018tc005138
|View full text |Cite
|
Sign up to set email alerts
|

Emplacement of the Triassic Pueblito Pluton, NW Colombia: Implications for the Evolution of the Western Margin of Pangea

Abstract: We present the first structural geology focused study of a Triassic pluton in the Northern Andes, which provides new insights into the understanding of the tectonically complex northwestern corner of South America. Based on a combination of field structural data (377 stations) and a detailed magnetic susceptibility survey, 159 sites, we studied the structure of the Pueblito Pluton (PP), an original suprasubduction mafic cumulate structure emplaced in the northern part of the Arquia Terrane (western margin of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 82 publications
0
2
0
1
Order By: Relevance
“…This vorticity value denotes that the CPPF was a contractional fault during this period. The vertical to sub‐vertical foliation with sub‐horizontal lineations also favors this idea (e.g., Garza et al., 2021; Rodriguez‐Jimenez et al., 2018). However, the middle‐stage granitoid possesses the broadest exposure area but the shortest emplacement time interval among the three stages, which points to a rapid magma ascent and accretion process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This vorticity value denotes that the CPPF was a contractional fault during this period. The vertical to sub‐vertical foliation with sub‐horizontal lineations also favors this idea (e.g., Garza et al., 2021; Rodriguez‐Jimenez et al., 2018). However, the middle‐stage granitoid possesses the broadest exposure area but the shortest emplacement time interval among the three stages, which points to a rapid magma ascent and accretion process.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies on large‐scale batholiths emplaced at shear zone, which are usually incrementally constructed by a series of magma batches with construct durations up to several millions of years (Annen et al., 2015; Bartley et al., 2008; Coleman et al., 2004; de Saint Blanquat et al., 2011; Glazner et al., 2004; Miller et al., 2011; Paterson et al., 2011), had revealed that magma ascent and emplacement, space‐creation, and accretion process were strongly affected by regional tectonics (e.g., Blanquat et al., 1998; Garza et al., 2021; Hutton, 1988; Ingram & Hutton, 1994; Rodriguez‐Jimenez et al., 2018; Rosenberg, 2004; Salazar et al., 2016; Tikoff & Greene, 1997). Therefore, the kinematic evolution of the region that suffered from multiple tectonic events has been successfully reestablished through analysis of internal fabrics of syntectonically emplaced plutons (e.g., Archanjo et al., 1994; Benn et al., 2001; Blanquat et al., 1998; Borradaile & Dehls, 1993; Chatterjee et al., 2020; Mamtani, 2014; Mamtani et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Edades radiométricas de estas unidades y de cuerpos ígneos Triásicos, que intruyen las secuencias metasedimentarias del Complejo Arquía (e.g. Diorita de Pueblito con edad U-Pb en circón de 233±14 Ma y 236±15 Ma, Rodríguez-Jiménez et al, 2018; Stock de Amagá con edad U-Pb en circón de 227,6±4,5 Ma, Vinasco et al, 2006), indican protolitos sedimentarios del Paleozoico e ígneos del Triásico, y eventos de metamorfismo del Pérmico y Cretácico (Tablas S1 y S3). Figura 1.…”
Section: Marco Geológicounclassified